VD_FINDINFO AI 336/10 - 86/2011 vom 23. Februar 2011 - VD Tribunal cantonal (2011)
LOI FÉDÉRALE SUR L'ASSURANCE-INVALIDITÉ, RÉVISIONPRESTATION D'ASSURANCE, TRANSACTIONACCORD | 17 LPGA, 50 LPGA, 88a RAI